High-reflection cooling fabric based on nano inorganic material compound coating and preparation method of high-reflection cooling fabric

By printing a nano-inorganic material composite coating on a polyester fabric substrate, the problem of low fabric reflection efficiency is solved and an efficient cooling effect is achieved, which is suitable for thermal management and energy-saving textiles in high temperature environments.

CN120797394APending Publication Date: 2025-10-17NANTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511110294.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing fabrics have low reflective efficiency in high-temperature environments, making it difficult to effectively reduce the heat on the human body surface, affecting comfort and safety.

Method used

A composite coating of nano-inorganic materials, including barium sulfate, zinc oxide and titanium dioxide, is printed on a polyester fabric base through a paint printing method to form a highly reflective cooling fabric.

Benefits of technology

It significantly improves the light reflectivity of the fabric within the solar spectrum, provides efficient cooling performance, and is suitable for thermal management and energy-saving textiles in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120797394A_ABST
    Figure CN120797394A_ABST
Patent Text Reader

Abstract

The invention discloses a high-reflection cooling fabric based on a nano inorganic material compound coating and a preparation method of the high-reflection cooling fabric, and relates to the technical field of textiles. The high-reflection cooling fabric comprises a polyester fabric substrate and a coating printed on the surface of the substrate, the coating comprises at least two nano inorganic materials of barium sulfate, zinc oxide and titanium dioxide. The nano coating compounded by barium sulfate, zinc oxide and titanium dioxide is printed on the surface of the polyester substrate, so that the light reflection capability of the fabric in a solar spectrum range is remarkably improved, the fabric is particularly suitable for the fields of human body heat management and energy-saving textiles in a high-temperature environment, and the limitation that a traditional cooling fabric is low in reflection efficiency and poor in durability is broken through; a novel solution with efficient cooling and long-term stability is provided for the fields of outdoor worker protective clothing, building sunshade materials and the like, and meanwhile the application potential of functional textiles in energy conservation and consumption reduction is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of textiles, in particular to a high-reflective cooling fabric based on a nano-inorganic material compound coating and a preparation method thereof. BACKGROUND

[0002] With the frequent occurrence of global climate change and extreme weather events, the greenhouse effect and urban heat island effect are becoming more and more serious, making the number of high-temperature weather in summer more and more prolonged. High-temperature weather brings great challenges to human production and life. On the one hand, high-temperature weather will cause social and economic decline. The related industries of outdoor work (such as construction, agriculture) will be forced to adjust the working hours, causing economic losses; high-temperature drought leads to reduced crop yields and livestock breeding, thereby increasing the prices of food and meat. On the other hand, high-temperature weather has a great impact on human health. High-temperature weather can cause heat stroke, heat exhaustion, and even heat stroke in severe cases; high temperature can aggravate the burden on the heart and easily induce cardiovascular and cerebrovascular diseases, especially for the elderly and patients with chronic diseases; high temperature exacerbates air pollution (such as the rise of ozone concentration), which may cause asthma, chronic obstructive pulmonary disease, etc.

[0003] Textiles, as the second skin of the human body, play a crucial role in resisting external environmental temperature changes. Heat-regulating clothing that regulates human body temperature by controlling fabric performance has gradually become a hot research field of concern. In high-temperature environments, fabrics not only need to have excellent protective functions, but also need to effectively dissipate heat under high-temperature conditions to reduce the heat on the human body surface, thereby ensuring the comfort and safety of personnel or equipment. In the summer outdoors, heat mainly comes from solar energy. The core of high-reflective cooling is to reduce heat absorption through efficient reflection of sunlight on the surface of the material. Passive cooling, as a passive input cooling technology, can achieve zero energy consumption and zero pollution self-cooling, providing an innovative solution to cope with environmental changes and regulate human thermal comfort, which has important practical significance. SUMMARY

[0004] The purpose of the present application is to provide a high-reflective cooling fabric based on a nano-inorganic material compound coating and a preparation method thereof to solve the problems existing in the prior art.

[0005] To achieve the above purpose, the present application provides the following solutions:

[0006] One of the technical solutions of the present application: a high-reflective cooling fabric based on a nano-inorganic material compound coating is provided, which comprises a polyester fabric substrate and a coating printed on the surface of the substrate; the coating comprises nano-inorganic materials; the nano-inorganic materials are at least two of barium sulfate, zinc oxide and titanium dioxide.

[0007] As a further preferred embodiment of the present application, when the nanomaterial in the coating is a combination of zinc oxide and barium sulfate, the mass ratio of zinc oxide and barium sulfate is (1-7):(1-5).

[0008] As a further preferred embodiment of the present application, the mass ratio of zinc oxide and barium sulfate is 1:1, 3:1, 4:1, 5:1, 6:1, 7:1, 1:3 or 1:5.

[0009] As a further preferred embodiment of the present application, when the nanomaterial in the coating is a combination of titanium dioxide and zinc oxide, the mass ratio of titanium dioxide and zinc oxide is (1-3):(1-3).

[0010] As a further preferred embodiment of the present application, the mass ratio of titanium dioxide and zinc oxide is 1:1, 1:3 or 3:1.

[0011] As a further preferred embodiment of the present application, when the nanomaterial in the coating is a combination of barium sulfate, zinc oxide and titanium dioxide, the mass ratio of barium sulfate, zinc oxide and titanium dioxide is (2-6):(1-5)

[0012] As a further preferred embodiment of the present application, the mass ratio of barium sulfate, zinc oxide and titanium dioxide is 6:1:3, 6:1:1, 2:4:4 or 6:3:1.

[0013] As a further preferred embodiment of the present application, the coating is printed by a pigment printing method.

[0014] The second technical solution of the present application provides a preparation method of the high-reflective cooling fabric based on the nanometer inorganic material compound coating, comprising the following steps:

[0015] At least two of barium sulfate, zinc oxide and titanium dioxide are formulated into a color paste, and then the color paste is printed on the surface of the polyester fabric substrate to form a coating, thereby obtaining the high-reflective cooling fabric based on the nanometer inorganic material compound coating.

[0016] As a further preferred embodiment of the present application, the concentration of the color paste is 50wt%-90wt%, and the thickness of the coating is 10-100μm.

[0017] The present application has the following technical effects:

[0018] The present application provides a high-reflective cooling fabric based on a nanometer inorganic material compound coating, which significantly improves the light reflection ability of the fabric in the solar spectrum range by printing a nanometer coating compounded by barium sulfate, zinc oxide and titanium dioxide on the surface of a polyester substrate, and is especially suitable for human body thermal management and energy-saving textile field in high temperature environment.

[0019] The application breaks through the limitation of low reflection efficiency and poor durability of traditional cooling fabrics, and provides a new solution with high cooling efficiency and long-term stability for outdoor worker protective clothing, building sunshade materials, vehicle textiles and other fields, and expands the application potential of functional textiles in energy saving and consumption reduction. BRIEF DESCRIPTION OF DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed in the embodiments will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor on the basis of these drawings.

[0021] Figure 1 (a) and SEM electron microscope picture (b) of the polyester fabric.

[0022] Figure 2 In the figure, (a) is the reflectivity of the polyester fabric in the range of 380-2500nm, and (b) is the temperature rising and falling curve of the polyester fabric under the sunlight simulator with light intensity of 1000W / m 2 .

[0023] Figure 3 (a) and SEM electron microscope picture (b) of the polyester fabric after printing nano inorganic material coating.

[0024] Figure 4 Reflectivity of the fabric coated with two-component ZnO and BaSO4 in the range of 380-2500nm.

[0025] Figure 5 Temperature rising and falling curve of the fabric coated with two-component ZnO and BaSO4 under the sunlight simulator with light intensity of 1000W / m 2 for 340s.

[0026] Figure 6 Reflectivity curve of the fabric coated with two-component ZnO and TiO2 in the full spectrum of sunlight.

[0027] Figure 7 Temperature rising and falling curve of the fabric coated with two-component ZnO and TiO2.

[0028] Figure 8 Reflectivity of the fabric coated with three-component ZnO, BaSO4 and TiO2 in the range of 380-2500nm.

[0029] Figure 9 Temperature rising and falling curve of the fabric coated with three-component ZnO, BaSO4 and TiO2 under the sunlight simulator with light intensity of 1000W / m 2Temperature rise and fall curves of the solar simulator irradiation 340s.

[0030] Figure 10 In particular, (a) is the temperature rise and fall curves of the solar simulator irradiation 340s of the three-component coated fabric (ZnO:BaSO4:TiO2=6:1:1), (b) is the linear fitting curve between the solar simulator light intensity and the coated fabric temperature, (c) is the stability of the coated fabric for five times of temperature rise / fall cycles, and (d) is the real-time temperature change curve of the coated fabric under the solar simulator (1000 W / m 2 ) irradiation for 1800s. DETAILED DESCRIPTION

[0031] The detailed description set forth below of various example implementations of the application describes and discloses only the particular implementations of the application and is not intended to limit the application to these particular implementations. Furthermore, each example implementation is intended to cover all alternatives, modifications and equivalents falling within the scope of the present application.

[0032] It is to be understood that the terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the application. In addition, for a range of values of a parameter, unless otherwise stated, each intervening value by each intervening value, as well as each smaller range "bounding" the range is also specifically disclosed. The above description is that of current implementations of the application. Various alterations and changes can be made without departing from the spirit and broader aspects of the application as set forth. The above specification, examples and data

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, preferred methods and materials are described. All publications mentioned herein are incorporated by reference to disclose and describe the methods and / or materials in connection with which the publications are cited. The citation of any reference is not an admission that it is prior art with respect to the present application. All documents introduced herein are incorporated by reference to the same extent as if each individual document was specifically and individually indicated to be incorporated by reference.

[0034] Many modifications and variations of this application can be made without departing from its spirit and scope, which is described in the scope of the application. Other implementations of the application will be apparent to those skilled in the art from consideration of the specification and practice of the application disclosed herein. The specification and examples given are exemplary only. It is to be understood that the application is not limited in any way by the

[0035] As used herein, the terms "comprise", "comprising", "include", "including", "have", "having" and the like are open-ended and do not exclude the presence of other elements or steps.

[0036] One of the purposes of the present application: to provide a high-reflective cooling fabric based on nano-inorganic material compound coating, comprising a polyester fabric substrate, and a coating printed on the surface of the substrate; the coating comprises nano-inorganic material; the nano-inorganic material is at least two of barium sulfate, zinc oxide and titanium dioxide.

[0037] Preferably, when the nano material in the coating is a compound of both zinc oxide and barium sulfate, the mass ratio of zinc oxide to barium sulfate is (1-7):(1-5).

[0038] Preferably, the mass ratio of zinc oxide to barium sulfate is 1:1, 3:1, 4:1, 5:1, 6:1, 7:1, 1:3 or 1:5.

[0039] Preferably, when the nano material in the coating is a compound of both titanium dioxide and zinc oxide, the mass ratio of titanium dioxide to zinc oxide is (1-3):(1-3).

[0040] Preferably, the mass ratio of titanium dioxide to zinc oxide is 1:1, 1:3 or 3:1.

[0041] Preferably, when the nano material in the coating is a compound of barium sulfate, zinc oxide and titanium dioxide, the mass ratio of barium sulfate, zinc oxide and titanium dioxide is (2-6):(1-5).

[0042] Preferably, the mass ratio of barium sulfate, zinc oxide and titanium dioxide is 6:1:3, 6:1:1, 2:4:4 or 6:3:1.

[0043] Preferably, the coating is printed by the pigment printing method.

[0044] The second purpose of the present application: to provide a preparation method of the above-mentioned high-reflective cooling fabric based on nano-inorganic material compound coating, comprising the following steps:

[0045] At least two of barium sulfate, zinc oxide and titanium dioxide are prepared into a color paste, and then the color paste is printed on the surface of the polyester fabric substrate to form a coating, thereby obtaining the high-reflective cooling fabric based on nano-inorganic material compound coating.

[0046] The present application will be further described in detail below in conjunction with examples. It should be pointed out that the parts of the present application not described in detail are conventional operating means in the art and are not the focus of the present application.

[0047] Example 1

[0048] The polyester fabric substrate used in the examples of the present application has a grammage of 75 g / m 2 , and has the characteristics of lightness, thinness and softness, Figure 1The optical photograph (a) and microscopic morphology (b) show that the selected fabric has typical woven fabric structure characteristics, with obvious pore structure between yarns.

[0049] The reflectivity of pure polyester fabrics in the solar spectrum (380-2500nm) is less than 60% ( Figure 2 a). When under the solar simulator (light intensity of 1000W / m 2 ) After irradiation for 340s, the surface temperature of the fabric reached 44℃( Figure 2 b).

[0050] Figure 3 A photo (a) and SEM image (b) of polyester fabric after nanoparticle coating (ZnO:BaSO4:TiO2 = 6:1:1) are shown. As can be seen, the fabric surface becomes smoother and the texture is less pronounced after nanoparticle coating, and the nanoparticles in the coating are evenly distributed.

[0051] Table 1 shows the coating formulas with different proportions of ZnO and BaSO4 particles. The two-component coated fabric (coating thickness 40 μm) was prepared by a coating machine.

[0052] Figure 4 It is the reflectivity of the two-component ZnO and BaSO4 coated fabric in the 380-2500nm band.

[0053] Figure 5 The double-component ZnO and BaSO4 coated fabric was subjected to a light intensity of 1000W / m 2 The heating and cooling curves of the solar simulator for 340 seconds.

[0054] From the reflectivity curve of the fabric, it can be seen that the reflectivity of the fabric is better when the ZnO content in the coating composite formula is higher than that of BaSO4. When ZnO:BaSO4=6:1, the average reflectivity of the coated fabric in the full spectrum is the highest ( Figure 4 From the temperature rise and fall curves of the fabric under the solar simulator, it can be seen that the fabric has the best cooling performance when the coating formula is ZnO:BaSO4=6:1 ( Figure 5 ).

[0055] Table 1 Two-component ZnO and BaSO4 coating formula

[0056]

[0057] Table 2 shows the coating formulas with different proportions of ZnO and TiO2 particles. The two-component coated fabric (coating thickness 40 μm) was prepared by a coating machine.

[0058] Table 2 Two-component TiO2 and ZnO coating formulations

[0059]

[0060] Figure 6 The reflectivity curve of the coated fabric with the dual-component complex coating of ZnO and TiO2 in the full-spectrum band of sunlight. As can be seen from the figure, the reflectivity of the coated fabric is the highest when TiO2:ZnO = 1:1. Figure 7 The temperature rise and fall curve of the coated fabric with the dual-component complex coating of ZnO and TiO2. The temperature fall performance of the coated fabric is the best when TiO2:ZnO = 1:1.

[0061] The data obtained through the complex research of the dual components show that the synergistic effect between different nanoparticles has a significant influence on the performance of the fabric.

[0062] The coated fabric is prepared by further complexing BaSO4, ZnO and TiO2 nanoparticles. Table 3 is the coating formula of BaSO4, ZnO and TiO2 in different proportions, and three-component coated fabrics (coating thickness 40 μm) are prepared by a coating machine. As can be seen from the reflectivity curve of the coated fabric in Figure 8 , when the ratio of ZnO:BaSO4:TiO2 is 6:1:1, the reflectivity of the fabric reaches the highest. As can be seen from the temperature rise and fall curve of the coated fabric in Figure 9 , the temperature fall performance of the coated fabric with the ratio is also the strongest.

[0063] The temperature rise and fall curve of the coated fabric (ZnO:BaSO4:TiO2 = 6:1:1) under the sunlight simulator with different light intensities is shown in Figure 10 a. With the increase of the sunlight intensity, the temperature of the coated fabric also increases, and there is a linear relationship between the highest temperature and the light intensity ( Figure 10 b). In addition, the coated fabric exhibits good stability. After the coating experiences 5 temperature rise / fall cycles under the sunlight simulator, the highest temperature of the fabric still remains consistent with the initial state ( Figure 10 c). Figure 10 d is the temperature change of the coated fabric after the coated fabric is irradiated under the sunlight for 30 min. As can be seen from the figure, under the long-term radiation of the sunlight, the highest temperature of the fabric only fluctuates in a small range, indicating the stability of the performance of the coating.

[0064] Table 3 Three-component coating formula of BaSO4, TiO2 and ZnO

[0065]

[0066] The above described embodiments are only to illustrate the preferred modes of the present application, and are not intended to limit the scope of the present application. Any modification and improvement made by those skilled in the art to the technical solutions of the present application without departing from the design spirit of the present application shall fall within the protection scope of the present application.

Claims

1. A high-reflective cooling fabric based on a nano-inorganic material composite coating, characterized in that: The invention comprises a polyester fabric substrate and a coating printed on the surface of the substrate; the coating comprises a nano inorganic material; the nano inorganic material is at least two of barium sulfate, zinc oxide and titanium dioxide.

2. The high-reflective cooling fabric based on a nano-inorganic material composite coating according to claim 1, characterized in that: When the nanomaterial in the coating is a mixture of zinc oxide and barium sulfate, the mass ratio of zinc oxide to barium sulfate is (1-7): (1-5).

3. The high-reflective cooling fabric based on the nano-inorganic material composite coating according to claim 2 is characterized in that: The mass ratio of zinc oxide to barium sulfate is 1:1, 3:1, 4:1, 5:1, 6:1, 7:1, 1:3 or 1:

5.

4. The high-reflective cooling fabric based on a nano-inorganic material composite coating according to claim 1, characterized in that: When the nanomaterial in the coating is a mixture of titanium dioxide and zinc oxide, the mass ratio of titanium dioxide to zinc oxide is (1-3): (1-3).

5. The high-reflective cooling fabric based on a nano-inorganic material composite coating according to claim 4, characterized in that: The mass ratio of titanium dioxide to zinc oxide is 1:1, 1:3 or 3:

1.

6. The high-reflective cooling fabric based on a nano-inorganic material composite coating according to claim 1, characterized in that: When the nanomaterial in the coating is a mixture of barium sulfate, zinc oxide and titanium dioxide, the mass ratio of barium sulfate, zinc oxide and titanium dioxide is (2-6): (1-5): (1-4).

7. The high-reflective cooling fabric based on a nano-inorganic material composite coating according to claim 6, characterized in that: The mass ratio of barium sulfate, zinc oxide and titanium dioxide is 6:1:3, 6:1:1, 2:4:4 or 6:3:

1.

8. The high-reflective cooling fabric based on a nano-inorganic material composite coating according to claim 1, characterized in that: The coating is printed by a pigment printing method.

9. A method for preparing a high-reflective cooling fabric based on a nano-inorganic material composite coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: At least two of barium sulfate, zinc oxide and titanium dioxide are prepared into a color paste, and then the color paste is printed on the surface of the polyester fabric substrate to form a coating, thereby obtaining the high-reflective cooling fabric based on the nano-inorganic material composite coating.